(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2025)
English stress, a key suprasegmental feature, remains a major challenge for Nigerians learning English as a second language. While previous studies have examined intonation, performance, and varieties of Nigerian English, limited attention has been given to stress in compound words. This study investigated stress assignment patterns among prospective English language teachers (PELTS) in universities across South-West Nigeria. A mixed-methods design was employed, involving 100 PELTs from four universities. Data were collected through a 20-word corpus analyzed with PRAAT Speech Analysis Software and a survey questionnaire. Guided by Metrical Phonology and Cognitive Social Learning theories, the study analyzed pitch, intensity, and duration across native and non-native groups. Findings revealed consistent difficulty among PELTs in assigning stress correctly to compound words, affecting pronunciation intelligibility. The study recommends targeted phonological training, integration of speech technology, and curriculum reforms to enhance stress competence among future teachers.